Thematic issue of the Second combined Bio-ontologies and Phenotypes Workshop. Issue 1 (December 2016) - Verspoor, Karin; Oellrich, Anika; Collier, Nigel; Groza, Tudor; Rocca-Serra, Philippe; Soldatova, Larisa; Dumontier, Michel; Shah, Nigam
Abstract This special issue covers selected papers from the 18th Bio-Ontologies Special Interest Group meeting and Phenotype Day, which took place at the Intelligent Systems for Molecular Biology (ISMB) conference in Dublin in 2015. The papers presented in this collection range from descriptions of software tools supporting ontology development and annotation of objects with ontology terms, to applications of text mining for structured relation extraction involving diseases and phenotypes, to detailed proposals for new ontologies and mapping of existing ontologies. Together, the papers consider a range of representational issues in bio-ontology development, and demonstrate the applicability of bio-ontologies to support biological and clinical knowledge-based decision making and analysis. The full set of papers in the Thematic Issue is available athttp://www.biomedcentral.com/collections/sig .